Pengaruh Kinerja Keuangan dalam Memprediksi Kondisi Financial Distress pada Bank Syariah di ASEAN Periode 2019-2023 - Arnanda, Putri Amalia; Sudarmawan, Barianto Nurasri (Universitas Batanghari Jambi, 2025)
This study aims to analyze the effect of financial performance on financial distress in Islamic banks in ASEAN for the period 2019-2023. The independent variables used include Return on Assets (RoA), Debt to Equity Ratio (DER), Current ratio (CR), Non-Performing Financing (NPF), and Capital Adequacy Ratio (CAR). Financial distress is measured using the Zmijewski model. The method used is panel data regression with a sample of 23 Islamic banks selected by purposive sampling. The results of the analysis show that RoA, CR, and CAR have a significant negative effect on financial distress, indicating that good profitability, liquidity, and capital adequacy can reduce the possibility of financial difficulties. In contrast, DER and NPF do not show a significant effect, indicating that leverage and managed non-performing financing do not play a major role in predicting financial distress. This study emphasizes the importance of managing profitability, liquidity, and capital adequacy to reduce the risk of financial distress and improve the financial performance of Islamic banks in ASEAN.